Regional Innovative Development in the Context of Current Trends of Neo-Industrialisation - Doroshenko, Yury A.; Malykhina, Irina O.; Somina, Irina V. (Economy of Regions, 2020)
Russian economy is characterised by raw materials dependence, the impossibility of using the latest achievements of the sixth technological mode, rapid digital development, internationalisation of scientific and technological progress, the impact of technological shifts on structural transformations. These aspects lead to the implementation of an innovative scenario for the development of regions in the context of neo-industrial challenges, which is necessary for identifying and consolidating the most effective tools for innovating the modern Russian economy. This problem primarily affects regional economic systems with a set of innovative economic entities. To solve the problem, we analysed and generalised the scientific-theoretical, methodological framework, and practical aspects of regional innovative development, taking into account current trends and key parameters of neo-industrialisation. Considering neo-industrialisation in regional economic systems, the innovative development path increasingly depends on such critical parameters as human capital, intersectoral interaction, and technological modernisation processes. The paper presents scientific and theoretical substantiation of the possibilities of regional innovative development in the context of current trends of neo-industrialisation. Research methodology and tools include systemic, categorical, structural, and functional analysis, conceptual modelling. We identified and described objective factors, trends, and problems of ensuring the long-term regional innovative development. Further, we defined and classified the current trends of innovative development of the regional economy, as well as substantiated the key parameters of neo-industrialisation. Then, we created a model of regional innovative development. To explain the discrepancies between the actual and the desired level of the development of neo-industrialisation parameters, we presented an algorithm that allows identifying bottlenecks, forming a roadmap, and implementing a mechanism for strengthening the potential of regional innovative development. Additionally, we specified key aspects of the innovative development path of regions, considering the current state of the real sector. The obtained theoretical results can be used for forecasting the most important economic challenges and identifying strategic factors for the regional innovative development in the context of neo-industrialisation.